Carbodiimides: new materials applied as anode electrodes for sodium and lithium ion batteries. Issue 5 (14th January 2016) - Eguía-Barrio, A.; Castillo-Martínez, E.; Liu, X.; Dronskowski, R.; Armand, M.; Rojo, T.
Abstract : Carbodiimides for batteries: the family of transition-metal carbodiimides MNCN (M = Cu, Zn, Mn, Fe, Co, and Ni) are shown to be new electrochemically active materials through displacement reactions both for lithium and sodium ion batteries. Abstract : Conversely to the electrochemical inactivity claimed for MnNCN, we report here that transition-metal carbodiimides, MNCN (M = Cu, Zn, Mn, Fe, Co and Ni), are electrochemically active materials for electrochemical energy-storage systems. They exhibit high reversible capacities (200–800 mA h g −1 ) for lithium and sodium ion batteries, stored by means of conversion reactions.